Anosognosia for motor deficits in patients with left hemisphere lesions: a systematic review - Simioni, Maura; Basilico, Stefania; Gandola, Martina (Frontiers in Neurology, 2025)
BackgroundPatients with brain damage may deny the presence of their contralesional motor deficits. Some individuals may even claim they performed specific actions with the paralyzed limb, such as clapping hands. This well-known condition, called anosognosia for motor deficits, has been more frequently associated with right-brain lesions, primarily involving the posterior parietal cortex, the frontal cortex, and the insula. Instances of anosognosia for motor deficits in patients with left hemispheric lesions have also been described. However, less is known about the underlying mechanisms or differences in clinical manifestation.MethodsFollowing PRISMA guidelines, the present systematic review investigated the prevalence of anosognosia for motor deficits in patients with left-hemispheric brain lesions, focusing on its severity, clinical manifestation, and anatomical correlates. Moreover, we review adopted assessment methods and discuss the potential role of handedness and atypical hemispheric specialization in determining anosognosia for motor deficits. A comprehensive search across multiple databases up to the 28th of February 2025 identified 893 studies, with 25 included in the present study.ResultsReported prevalence of anosognosia for motor deficits in left brain-damaged patients ranged from 3.6 to 50% of assessed patients. These wide-ranging estimates may reflect the high heterogeneity in the tools adopted to assess both motor deficits and anosognosia, as well as in the diagnostic criteria employed to define anosognosia itself. Lesional data, when provided, showed a substantial overlap with the distributed network identified as the lesion substrate of anosognosia following right-hemisphere damage.ConclusionAnosognosia for motor deficits following left-hemisphere lesions is less rare than previously assumed, thus challenging the hypothesis that the right hemisphere has an exclusive role in motor awareness. However, considering the sparsity and heterogeneity of current evidence, multicentric studies are required to better characterize the specific features of anosognosia associated with left-sided lesions and tackle unresolved issues such as the role of atypical hemispheric specialization.